A randomized controlled trial of exercise on augmenting the effects of cognitive remediation in persons with severe mental illness. (July 2021) - McGurk, Susan R.; Otto, Michael W.; Fulford, Daniel; Cutler, Zachary; Mulcahy, Leonard P.; Talluri, Sai Snigdha; Qiu, Wei Qiao; Gan, Qini; Tran, Ivy; Turner, Laura; DeTore, Nicole R.; Zawacki, Stacey A.; et al.
Abstract: Background: Preliminary evidence suggests that aerobic exercise may augment the effects of cognitive remediation on improving cognitive functioning in severe mental illness. It has also been hypothesized that increases in cognitive functioning associated with adding exercise are mediated by increases in brain derived neurotrophic factor (BDNF). However, rigorous controlled trials are lacking. Methods: A randomized controlled trial was conducted to explore whether adding a 30-h aerobic exercise program over 10 weeks to an equally intensive cognitive remediation program (CR + E) improved cognitive functioning more than cognitive remediation alone (CR-Only). Thirty-four participants with schizophrenia or bipolar disorder were randomly assigned to CR + E or CR-Only, and cognitive functioning was assessed at baseline and post-treatment. Total and mature BDNF were measured in blood serum at baseline, Week-5 pre- and post-exercise, and Week-10 pre- and post-exercise. Results: Participants in both conditions had high levels of engagement in the interventions and improved significantly in cognitive functioning, but did not differ in amount of cognitive change. The groups also did not differ in changes in BDNF from pre-to post-exercise at Weeks 5 or 10, nor in resting BDNF levels. Exploratory analyses indicated that higher body mass index (BMI) significantly predicted attenuated improvement in cognitive functioning for both groups. Discussion: Exercise did not augment the effects of cognitive remediation in persons with severe mental illness, possibly because the cognitive remediation program resulted in strong gains in cognitive functioning. Moderate aerobic exercise does not appear to reliably increase BDNF levels in persons with severe mental illness. ClinicalTrials.Gov Identifier: NCT02326389.